Economic Globalization: Impacts On Indonesian Import-Export Statistics - Zulfikar Hasan (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
Economic globalization is the manner of combining the national economy into the global financial system played by WTO, IMF and World Bank players. Economically the Indonesian state has a dependence on international trade, production and finance. Accordingly, the Indonesian nation unprotected to international pressure and globalization. Economic globalization has an impact on national commercial law which must resemble as an integration mechanism that can harmonize the various internal interests of the nation, national and international interests and between sectors of domestic life. Economically there are increasingly competing trade pressures, multi nationalization of production, integration of financial markets and inrush of global capital investment. In dealing with the impact of economic globalization using strategies play an active role in the process of negotiation with globalization actors and creating national commercial law, especially regarding the foreign investment that accommodates the interests of global values to appropriate for the development of the national economy. Globalization is also very instrumental in the volume of export and import in a country, including Indonesia, which will have an impact both negative and positive from globalizing products and services.